2012
DOI: 10.1111/j.1447-0756.2012.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endothelial nitric oxide synthase in the uterus of patients with leiomyoma or adenomyosis

Abstract: Based on the findings that the expression of endothelial nitric oxide synthase was significantly higher in the uterus with leiomyoma or adenomyosis, it can therefore be inferred that nitric oxide might have a pathological effect on the uterus with the above diseases. In particular, it is also presumed that endothelial nitric oxide synthase is closely associated with menorrhagia and dysmenorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…This increased local NO expression could cause activation of cyclooxygenase-2 and subsequently elevating the prostaglandins levels, such as prostaglandin E2 (34). On the other hand, the vascular expression of eNOS in our study, approves the findings by Gokdeniz et al, nevertheless their study mainly focuses on the muscular characteristics of myoma tissues (35) Although this study shows a non-significant increase in the expression of enzyme in vascular endothelium, this finding is not in contrast with results of Oh et al study (36) which found significant over-expression of enzyme in vasculature of the endothelium. Vascular over-expression of eNOS in case of uterine myoma may affect the biological integrity of endometrium.…”
Section: Discussionsupporting
confidence: 87%
“…This increased local NO expression could cause activation of cyclooxygenase-2 and subsequently elevating the prostaglandins levels, such as prostaglandin E2 (34). On the other hand, the vascular expression of eNOS in our study, approves the findings by Gokdeniz et al, nevertheless their study mainly focuses on the muscular characteristics of myoma tissues (35) Although this study shows a non-significant increase in the expression of enzyme in vascular endothelium, this finding is not in contrast with results of Oh et al study (36) which found significant over-expression of enzyme in vasculature of the endothelium. Vascular over-expression of eNOS in case of uterine myoma may affect the biological integrity of endometrium.…”
Section: Discussionsupporting
confidence: 87%
“…iNOS expression is higher in leiomyoma than in normal myometrial cells 7,51 . Moreover, the uterus with leiomyoma or adenomyosis exhibited a higher expression of endothelial NOS, especially in cases associated with symptoms (menorrhagia and dysmenorrhea) 12 . This result illustrates that NOS may be involved in the pathomechanisms of invasion and excess growth of myometrium, similar to the process of vessel formation.…”
Section: Discussionmentioning
confidence: 96%
“…In 2012, Aguilar-Melero P et al (Aguilar-Melero et al, 2012) indicated the significant association of NOS3 and cell survival in a hepatoma cell line. While Oh et al (2013) observed the expression of endothelial nitric oxide synthase was significantly higher in the uterus with leiomyoma or adenomyosis. When investigating the functions of the NOS3 gene in cancers, Terrazzino et al (2012) suggested NOS3 might be the marker for predicting acute skin toxicity in breast cancer patients receiving radiotherapy.…”
Section: Nitric Oxide Synthase 3 Gene Variants and Colorectal Cancer:mentioning
confidence: 72%